2022
DOI: 10.3389/fnut.2022.1029119
|View full text |Cite
|
Sign up to set email alerts
|

Variation of vitamin B contents in maize inbred lines: Potential genetic resources for biofortification

Abstract: Vitamin B and its derivatives possess diverse physiological functions and are essential micronutrients for humans. Their variation in crops is important for the identification of genetic resources used to develop new varieties with enhanced vitamin B. In this research, remarkable variations were observed in kernels of 156 maize inbred lines, ranging from 107.61 to 2654.54 μg per 100 g for vitamin B1, 1.19–37.37 μg per 100 g for B2, 19.60–213.75 μg per 100 g for B3, 43.47–590.86 μg per 100 g for B5, and 138.59–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Specifically, they are an essential source of carotenoids, phenolic compounds, and phytosterols. However, studies have indicated that the vitamin B content (B1, B2, B3, B5, and B6) in standard varieties of corn cultivated in America falls significantly short of meeting the daily recommended values (B1: 1.2 mg day −1 , B2: 1.3 mg day −1 , B3: 16 mg day −1 , B5: 5 mg day −1 , B6: 1.3 mg day −1 ) [24]. Efforts toward enhancing the nutritional value of corn through biofortification, particularly for provitamin A, vitamin B9 (folic acid), and vitamin E, have been explored by Blancquaert et al [25].…”
Section: Corn: From Feed To Biofuelmentioning
confidence: 99%
“…Specifically, they are an essential source of carotenoids, phenolic compounds, and phytosterols. However, studies have indicated that the vitamin B content (B1, B2, B3, B5, and B6) in standard varieties of corn cultivated in America falls significantly short of meeting the daily recommended values (B1: 1.2 mg day −1 , B2: 1.3 mg day −1 , B3: 16 mg day −1 , B5: 5 mg day −1 , B6: 1.3 mg day −1 ) [24]. Efforts toward enhancing the nutritional value of corn through biofortification, particularly for provitamin A, vitamin B9 (folic acid), and vitamin E, have been explored by Blancquaert et al [25].…”
Section: Corn: From Feed To Biofuelmentioning
confidence: 99%
“…Halm (1977) noted that little research had been conducted on the beverage's production, microbiology and nutritional value. Safiul Azam et al . (2022) conducted a survey and found that “ asaana ” has a short shelf life of three to six days when stored at room temperature and is often produced under unhygienic conditions with varying temperature based on the vendor or consumer.…”
Section: Ghanaian Local Beverages - the Case Of Asaanamentioning
confidence: 99%
“…Vitamin B1 (thiamine) and B3 (niacin) are essential nutrients found in maize. These vitamins play crucial roles in energy metabolism and are vital for maintaining good health [13][14][15]. However, their concentration can be influenced by storage conditions, potentially leading to a decrease in nutritional value [16].…”
Section: Introductionmentioning
confidence: 99%